Work Life Quality Role as A Variables of Knowledge Mediation, Spiritual Intelligence, And Attitudes Towards Nurse Performance in Applying Patient Safety (SKP) - Nurmaini Nurmaini; Kemala Rita Wahidi; Rian Adi Pamungkas (Penerbit Kemala Indonesia, 2021)
This study aims to analyse the significant influence together Knowledge, Spiritual Intelligence, and Attitude on the Quality of Work Life and the Impact on Nurse Performance in the Application of Patient Safety Targets at X Hospital either partially or simultaneously. The research methodology uses a quantitative approach with the path analysis method using the Structural Equation Modelling (SEM) equation. The sampling technique was carried out by saturated sampling (census) of 111 respondents based on the total population of nurses in the inpatient room. The results showed that Knowledge, Spiritual Intelligence, and Attitude had a significant influence together on the quality of work life and their impact on nurse performance. Thus, to improve nurse performance in implementing patient safety goals at X Hospital simultaneously such as knowledge has a significant positive effect on the quality of work life of nurses, spiritual intelligence has a significant positive effect on the quality of work life of nurses, attitudes have a significant positive effect on the quality of work life of nurses, knowledge has a significant positive effect on the performance of nurses in implementing patient safety goals, attitudes have a significant positive effect on the performance of nurses in implementing patient safety goals, and the quality of work life of nurses has a significant positive effect on the performance of nurses in implementing patient safety goals with seventh hypothesis. The findings of this study are that the quality of work life of nurses has a partially mediating role in the performance of nurses in implementing patient safety goals at X Hospital with 0.666 of correlation value. This is an increase in religious activities in kinship to form emotional bonds and commitment to nurses to behave calmly and patiently in implementing the Patient Safety Goals on an ongoing basis.